(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This paper surveyed the New Partnership for African Development (NEPAD), its agenda, strength and weaknesses vis-à-vis the raison d’etre for its establishment. It appraised the gains accruing to Africa in contradistinction to that of the developed world which discerned a yearning disparity. For Tony Blair (a former British Prime Minister), this partnership was not just about aid in its totality, it was not only about what we give, Africa needed our support and we needed Africa to succeed. It was how altruistic the likes of Tony Blair were that necessitated the review of the activities of NEPAD and its effect on Africa that claimed its patent. This was against the background of a persisting underdevelopment, especially the economic, of African countries and the poverty of their citizens. The manipulative operations of International Financial Institutions (IMF, World Bank-IBRD, among others) opened up African economies to exploitation with the unarguable connivance of rich multinational corporations and consultancy firms who maximized their profits from Africa’s misery and helplessness. The paper concluded that Western corporate power in Africa was a monster with a thousand stomachs, insatiable for profits. For Africans, this was a hard stuff to swallow - but corporate greed knew no limits. The comparative and the analytical were adopted.